Problem istoty małżeństwa oraz istoty zgody małżeńskiej. Refleksja antropologiczna - Góralski, Wojciech (Ius Matrimoniale, 2015)
The problem of the marriage essence, considered in close connection with matrimonial consent, without a doubt constitutes a difficult challenge for the jurisprudence in the field of matrimonial law. The question: what is marriage, what is the identity of marriage, in other words its essence, which arose at different stages of development of canon law, revived after the Second Vatican Council, which presented a partnership of life and love established by man and woman through a “matrimonial covenant of irrevocable personal consent” in a new light. Deep reflection on marriage as an institution of natural law orders, in search of its essence, to refer first of all to the natural dimension of the unity of two people in a complementary dimension of their masculinity and femininity, in other words in “their natures”. It is about the relationship of two people based on their personal esse, whose action constitutes an existential development. Significant legal nature of this relationship is based on the existence of una caro, unity “in the natures”, which is materialised through their knot of justice. When moving from possibilities to action, an indispensable factor is matrimonial consent of the parties indicating unity of two acts of will made with the same intentionality, resulting in a conjugal relationship.